China Water Forum 2022 - Zuo, Qiting; Wang, Fuqiang; Zhai, Jiaqi; Zhang, Xiuyu; She, Dunxian; Zou, Lei; Gan, Rong; Luo, Zengliang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We summarized China's water security status and issues based on the papers published in the Special Issue entitled "China Water Forum 2022". Our summaries and the published papers in this Special Issue are compiled into a reprint to help readers understand current research progresses on this topic.